(3eQCI GdYLGFH aj GdYed HGdLjH GdZGFHs - (3eMehO Hf CMeO GdChais
(3ChdgG (B:s
(3deG de jcf ddLjH GdZGFH , eDfg dcd WGdH MJi JjSQ Cf jVY HCdI s
(3BNQgG (B:s
(3aGdNGd Ydi bhS GdeWdhH ef eQcR GdCNQ hGddg CYde HMbjbg GdMGd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B52 - (3U(B61s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B3 - (3U (B576 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B95 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B1082) s
Keywords: (3Gdadcs